Geophysical Observatory in Kamchatka region for monitoring of phenomena connected with seismic activity - Uyeda, S.; Nagao, T.; Hattori, K.; Hayakawa, M.; Miyaki, K.; Molchanov, O.; Gladychev, V.; Baransky, L.; Chtchekotov, A.; Fedorov, E.; Pokhotelov, O.; Andreevsky, S.; et al. (Natural Hazards and Earth System Sciences, 2001)
Regular monitoring of some geophysical parameters in association with seismicity has been carried out since last year at the Japan-Russian Complex Geophysical Observatory in the Kamchatka region. This observatory was organized in connection with the ISTC project in Russia and was motivated by the results of the FRONTIER/RIKEN and FRONTIER/NASDA research projects in Japan. The main purpose of the observations is to investigate the electromagnetic and acoustic phenomena induced by the lithosphere processes (especially by seismic activity). The seismicity of the Kamchatka area is analyzed and a description of the observatory equipment is presented. At present, the activity of the observatory includes the seismic (frequency range ∆F = 0.5 – 40 Hz) and meteorological recordings, together with seismo-acoustic (∆F = 30 – 1000 Hz) and electromagnetic observations: three-component magnetic ULF variations ( ∆F = 0.003 – 30 Hz), three-component electric potential variations ( ∆F < 1.0 Hz), and VLF transmitter’s signal perturbations ( ∆F ~ 10 – 40 kHz).